A Reversing Case within Trajectories of Liberalisation: The revival of neo-corporatism in Austria since 2008 - Lehner, Lukas (Momentum Quarterly, 2017)
The overall dominating trend of liberalisation, deregulation and privatisation has accelerated since the global economic crisis in 2008. Under the paradigm of competitiveness, a major policy goal has been the implementation of ‘structural reforms’ replacing neo-corporatist practices with market coordination. However, Austria’s coordinating institutions have been strengthened since 2008, contrasting the EU-wide liberalising trend. To explain this puzzle, government members’ biographies since 1983 were analysed, seven elite interviews conducted and official government documents evaluated. Under the logic of access, social partner organisations made active use of a ‘revolving door effect’, placing their employees as ‘interlocking directorates’ in government positions to gain influence on policies. For this ‘power-policy exchange’ social partners defended political compromises of the government and supported the weakened social democratic (SPÖ) and the conservative (ÖVP) party leadership. Such a ‘tactical alliance’ is fragile, as it depends on the interest constellation of actors involved, but outlines the remaining scope for domestic politics in an age of increased liberalising pressures from globalisation and EU integration.